SOCIAL CONSEQUENCES OF ECONOMIC DOWNTURN (2008) IN LITHUANIA - Gruževskis, Boguslavas; Zabarauskaitė, Rasa (Ekonomika, 2010)
The world economic recession has a significant adverse impact on social economic development in Lithuania. The article aims at assessing the possible long-term social consequences of the economic downturn in Lithuania if no actions are taken from the Government, as well as at designing recommendations on the implementation of measures with a view to mitigate the consequences of the recession. The article analyses various social economic indicators in Lithuania with the aim to highlight the impact of the recent economic downturn on different aspects of living standards in the country. The article seeks to provide evidence on the critical need to address social problems in Lithuania as well as to outline the next steps to be taken to mitigate the negative consequences of the economic downturn. The analysis has shown that in Lithuania, the major negative social consequences of the economic decline for the population manifest themselves in job losses and income decrease, which in turn result in the rising long-term unemployment, growing social exclusion, higher emigration and other negative consequences. With regard to this, long-term negative consequences of the economic recession could be mitigated by addressing two vital issues, namely job losses and a decrease in household income in Lithuania.